2018
DOI: 10.3727/152599518x15173355843325
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Together: The Importance of Shared Emotional Memory in Event Experiences

Abstract: Drawing on the wider literature in the psychology and sociology of emotions and memory this study provides new insights into the formation and role of shared emotion in the memory of event experiences. The methodology draws together several data collection methods in order to capture the complexity of emotional response. Thick data are gathered from a single case study friendship pair using a combination of short surveys, physiological measures, photo elicitation, and paired interviews to provide a detailed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 76 publications
(89 reference statements)
2
57
0
1
Order By: Relevance
“…Surprisingly few studies have considered these aspects of collective experience within tourism although there are a growing number within event studies, for example, football (von Scheve and Ismer, 2013), festivals (Wood and Kenyon, 2018), event design (Richards et al, 2014) and 19 political events (Sterchele and Saint-Blancat, 2015). There has also been work on the related area of emotional attunement, music and festival experiences (e.g.…”
Section: Emotions Collective Experience and Communitasmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly few studies have considered these aspects of collective experience within tourism although there are a growing number within event studies, for example, football (von Scheve and Ismer, 2013), festivals (Wood and Kenyon, 2018), event design (Richards et al, 2014) and 19 political events (Sterchele and Saint-Blancat, 2015). There has also been work on the related area of emotional attunement, music and festival experiences (e.g.…”
Section: Emotions Collective Experience and Communitasmentioning
confidence: 99%
“…Although conceptual there is already some evidence for the process described here. For example, Wood and Kenyon's (2018) festival memories longitudinal study drew a number of 33 pertinent conclusions. These can be summarised as 1) memory detail (not accuracy) increases with time -false memories are subconsciously created through sharing and other experiences.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…O'Sullivan and Spangler (1998) describe experiences as having different levels of physical, mental, emotional, social, and spiritual activity. Christou, Sharpley, and Farmaki (2018) and Wood and Kenyon (2018) identified a link between emotions and satisfaction. Lazarus (1991) supports these findings by concluding that positive emotional experiences increase the likeliness that people perceive their lives as positive and desirable.…”
Section: Hedonic Satisfaction and Eudaimonic Satisfactionmentioning
confidence: 99%
“…This is perhaps surprising when others highlight the importance of memory in collective value creation and vibrant brand communities (Schau et al, 2009) and of the lasting narratives created from tourism experiences (Arnould and Price, 1993;Tung and Ritchie, 2011). Collective narratives are often formed around music memories (Van Dijck, 2006) and this is likely to be more intense when the musical experience was shared, as happens in an event setting (Wood and Kenyon, 2018). Manthiou et al (2014), in one of the few empirical studies into festival memory, found a strong relationship between the creation of vivid memories during the experience, and subsequent loyalty.…”
Section: Introductionmentioning
confidence: 99%